Research progress on the pharmacological effects of Baijiu based on its traditional efficacy - DING Junping, SONG Yan, HUANG Zhangjun, YU Songbai, LIU Rong, ZENG Nan (Zhongguo niangzao)
Baijiu, as China's national liquor, is deeply cherished by the public and has far reaching influence on China's economy and culture. With the outline of "Healthy China 2030", the influence of Baijiu on health has attracted much attention from scholars. Alcoholic beverage has been widely used and recorded in Chinese traditional medicine since ancient times. Modern pharmacological studies have shown that Baijiu has a certain effect on the body's cardiovascular and glucose metabolism. In this paper, the trace flavor substances (alcohols, acids, esters, phenols, nitrogen compounds and terpenes) in Baijiu were briefly introduced, and traditional effects recorded in ancient books and modern pharmacological action of Baijiu were summarized. The traditional effect of Baijiu was explained by modern pharmacological action, and the related mechanism of Baijiu effect was summarized, in order to provide scientific basis for Baijiu effect elucidating.